The overall survival rate for patients with hepatocellular carcinoma who underwent hepatic resection or radiofrequency ablation procedure for curative intent - Aisha K Al-Raddadi; Mohammed A Jameel; Alaa A Al-Zulfi; Waleed K Al-Shammari; Weam S Hussein; Ester A Robles; Faisal Al-Saif; Faisal Al-Alem; Abdulsalam Al-Sharabi; Ahmad Madkhali; Mazen Hassanain (Wolters Kluwer Medknow Publications, 2019)
Background: Hepatocellular carcinoma (HCC) is currently one of the leading causes of cancer-related deaths worldwide. According to the data obtained from the last Saudi Cancer Registry 2014, liver cancer represents 4.3% of all cancers diagnosed in Saudi Arabia. This study aimed to measure the overall outcome and "disease-free" survival rates of HCC patients who underwent either a liver resection or radiofrequency ablation (RFA) rehabilitation procedures in Riyadh, Saudi Arabia. Methods: A retrospective study was conducted in Riyadh, Saudi Arabia, examining 41 patients with HCC who underwent either liver resection or RFA with curative intent from 2011 to May 2016. The study took place in King Khalid University Hospital, Riyadh, Kingdom of Saudi Arabia, and utilized prospectively collected data. Among the patients who were studied, 7 patients underwent surgical resection and 34 patients underwent RFA. Patients' characteristics, overall survival (OS), and recurrence-free survival were analyzed. Results: Out of the 34 participants who underwent RFA, 17 (50%) experienced recurrence compared to only 3 (42.9%) participants who underwent liver resection. Seven (20.6%) patients who underwent RFA died out of a total of 34. However, only one patient (14.3%) from a total of seven who underwent liver resection died. Conclusion: When comparing the two treatment modalities, it was deemed that there was no significant difference in both recurrence and the OS in both groups.